Thoracoscopic resection of a rare atypical Type A thymoma: A case report - Miglani, Ripan K; Matta, Harshpreet; Kaur, Manjeet; Raja, Arun (Indian Journal of Case Reports, 2026)
Tumors originating from the thymic epithelium are distinctly uncommon, and within this already rare group, atypical Type A thymoma represents an exceptional pathological diagnosis. Fewer than 20 well-substantiated cases have been documented in the international literature, with only isolated reports emerging from the Indian subcontinent. We present a rare case of atypical Type A thymoma identified following surgical excision of an anterior mediastinal mass in a middle-aged patient. Radiological evaluation revealed a localized thymic lesion without distinctive features suggestive of aggressive or atypical histology, underscoring the inherent limitations of pre-operative assessment in such neoplasms. The patient underwent complete thoracoscopic resection with curative intent. Detailed histopathological analysis of the excised specimen demonstrated architectural and cytological features diagnostic of atypical type a thymoma, a conclusion that could only be established after complete tumor removal. The post-operative course was uneventful, and resection margins were free of disease. This report highlights the diagnostic obscurity and extreme infrequency of atypical Type A thymoma, emphasizing the indispensable role of surgical excision in establishing an accurate diagnosis. Given the scarcity of reported cases and the limited representation from India, this case contributes meaningful insight to the existing body of evidence and may aid in improving recognition, pathological interpretation, and clinical understanding of this exceedingly rare thymic epithelial tumor